Table of Contents and Front Matter - Larry Patton (Symphony in the Flint Hills, 2018)
This introduction to the 2018 Field Journal X, Waterways 2018, includes the table of contents, editorial committee information, sponsor information, the mission statement of Symphony in the Flint Hills, and art work and photography by various artists. BNSF Railway is proud to partner with Symphony in the Flint Hills through 2021 as a Major Presenting Sponsor in celebration of the prairie their rails pass through. The 2018 Symphony in the Flint Hills was held at the Rosalia Ranch in the heart of the Flint Hills.